Prevalence of intestinal parasites in the area of Parma during the year 2005 - Peruzzi, S.; Gorrini, C.; Piccolo, et al., G. (Acta Biomedica Atenei Parmensis, 2006)
Background and aim of the work: Intestinal parasitosis represent a relevant clinical problem, especially in developing countries, where they are responsible for morbidity and mortality in adults and children and many epidemiological data are available for these areas. The actual situation of intestinal parasitosis in Europe is not yet well investigated since they are usually not notified.We describe the occurrence of intestinal parasitosis in our laboratory from January to December 2005. Methods:We considered all patients (1117) whose stool samples were sent to our laboratory with the suspect of intestinal parasitosis during the year 2005. Each specimen was subjected to macroscopic and microscopic examination to demonstrate the presence of worm eggs, larvae, protozoan trophozoites or cysts and to an immunochromatographic assay to detect Giardia intestinalis and Cryptosporidium spp. specific antigens. Cultures for protozoa and helminths were carried out and a PCR specific for Entamoeba histolytica/Entamoeba dispar was also performed. Results: Our results indicated that 148 patients (13,24%) were affected by intestinal parasitosis. Among the 951 Italians, 96 (10%) were infected, while out of a total of 166 foreigners 52 had intestinal parasitosis (31%). Moreover, we found that 113 infections were caused by only one parasite while 35 were mixed infections. Conclusions: Intestinal parasitosis represent a remarkable cause of gastrointestinal disease and our study demonstrates that these infections are quite common in our area, affecting both Italians and non European citizens from developing countries.